2011
DOI: 10.1007/s10616-011-9364-7
|View full text |Cite
|
Sign up to set email alerts
|

Transition of basic protein during spermatogenesis of Fenneropenaeus chinensis (Osbeck, 1765)

Abstract: According to the ultrastructural characteristic observation of the developing male germ cells, spermatogenesis of the crustacean shrimp, Fenneropenaeus chinensis, is classified into spermatogonia, primary spermatocytes, secondary spermatocyte, four stages of spermatids, and mature sperm. The basic protein transition during its spermatogenesis is studied by transmission electron microscopy of ammoniacal silver reaction and immunoelectron microscopical distribution of acetylated histone H4. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 41 publications
1
18
0
1
Order By: Relevance
“…The existence of mitochondria‐like structures in penaeid spermatozoa has been confirmed in the cytoplasm of P. monodon , P. kerathurus , P. japonicus , F. paulensis , and F. chinensis (Medina et al, ; Ge et al, ; Braga et al, ). The change of mitochondrial morphology, especially the degeneration and disappearance of cristae, is presumably associated with the corresponding immobile character of the mature sperm cell (Tudge, ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The existence of mitochondria‐like structures in penaeid spermatozoa has been confirmed in the cytoplasm of P. monodon , P. kerathurus , P. japonicus , F. paulensis , and F. chinensis (Medina et al, ; Ge et al, ; Braga et al, ). The change of mitochondrial morphology, especially the degeneration and disappearance of cristae, is presumably associated with the corresponding immobile character of the mature sperm cell (Tudge, ).…”
Section: Discussionmentioning
confidence: 91%
“…Sandwiched between the nuclear region and the acrosomal vesicle, the shape and inner materials of the subacrosomal area vary greatly in the different penaeid species. P. monodon , F. chinensis , L. vannamei , L. stylirostris , L. occidentalis , and P. kerathurus all have a concave subacrosomal area, whereas P. japonicus and F. paulensis possess a flat structure (Medina et al, ; Alfaro et al, ; Ge et al, ; Braga et al, ). Our study showed the subacrosomal area of P. monodon spermatozoa in the spermatophore appeared less electron‐lucent and flocculent than the capacitated spermatozoa in the thelycum, as noted by Pongtippatee et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Kurtz et al (2009) and Li et al (2017) found that histone H3 in the sperm nuclei of the brachyuran crab is acetylated. The noncondensed nucleus may be caused by remanent acetylated histone H4 accompanied by chromatin fibers in Fenneropenaeus chinensis (Ge et al, 2011). Additionally, histone H3 methylation is important for sperm functioning and embryonic development, and histone H3 lysine 4 trimethylation (H3K4me3) plays a critical role in chromatin condensation and mitotic division during male gametogenesis (Pinon, Yao, Dong, & Shen, 2017;Song et al, 2011;Spina et al, 2014;Verma et al, 2015).…”
Section: Histone Modifications Regulate Chromatin Statusmentioning
confidence: 99%
“…Earlier research indicated that the chromatin of crustacean sperm is not highly packaged due to a lack of basic proteins. However, several studies on Cancer pagurus (Kurtz, Martínez-Soler, Ausió, & Chiva, 2008), Cancer magister (Kurtz et al, 2008), Maja brachydactyla (Kurtz, Ausió, & Chiva, 2009), Portunus pelagicus (Stewart et al, 2010), Fenneropenaeus chinensis (Ge et al, 2011), Astacus (Niksirat, James, Andersson, Kouba, & Kozák, 2015), and Eriocheir sinensis (Li et al, 2017;Wu et al, 2016;Wu, Kang, Guo, Mu, & Zhang, 2015;Zhang et al, 2016) have indicated that these decapod spermatozoal nuclei have a common characteristic, namely, that they contain parts of histones and some histone modifications. Because of the diversity of crustacean species, an integrated understanding of the origin of this special decapod sperm nuclei has not been achieved.…”
mentioning
confidence: 99%
“…Fenneropenaeus chinensis (Ge et al, 2011) and Litopenaeus vannamei (Alfaro-Montoya et al, 2017). There has been no specific study on the complete spermatogenesis of P. monodon.…”
Section: Spermatogenesis In Penaeid Prawnsmentioning
confidence: 99%